2013
DOI: 10.4136/ambi-agua.1129
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of free-living protozoa in aquatic environments of a Brazilian semi-arid region

Abstract: Free-living protozoa organisms are distributed in aquatic environments and vary widely in both qualitative and quantitative terms. The unique ecological functions they exhibit in their habitats help to maintain the dynamic balance of these environments. Despite their wide range and abundance, studies on geographical distribution and ecology, when compared to other groups, are still scarce. This study aimed to identify and record the occurrence of freeliving protozoa at three points in Piancó-Piranhas-Açu basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Of these, it was possible to identify 20 new taxain P1 and 10 taxa in P2 (Table 2). These values corroborate with those observed in other studies (PAULETO et al, 2009;VELHO et al, 2013, COLZANI, ALVES, 2013, KÜPPERS, CLAPS, 2012, MEDEIROS et al, 2013, which registered values between 22 and 65 species in cultivations. The difference found between the numbers of taxa identified in the readings taken on the day of collection concerning the cultures can be explained by the fact that the protozoa are encysted at the time of collection.…”
Section: Succession Of Species In Cultivation Conditionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of these, it was possible to identify 20 new taxain P1 and 10 taxa in P2 (Table 2). These values corroborate with those observed in other studies (PAULETO et al, 2009;VELHO et al, 2013, COLZANI, ALVES, 2013, KÜPPERS, CLAPS, 2012, MEDEIROS et al, 2013, which registered values between 22 and 65 species in cultivations. The difference found between the numbers of taxa identified in the readings taken on the day of collection concerning the cultures can be explained by the fact that the protozoa are encysted at the time of collection.…”
Section: Succession Of Species In Cultivation Conditionsupporting
confidence: 93%
“…and Arcella sp. in Brazilian water sources (LANSAC-TÔHA et al, 2000;VELHO et al, 2000;MEDEIROS et al, 2013). Godinho (2008) and Godinho (2003), in studies carried out in tropical environments, reported the association relationships between Thecamoebae and aquatic macrophytes, which could justify the presence of these organisms in P1 and P2 since in both places there is the presence of vegetation in the water sources margins.…”
Section: Taxonomy and Composition Of Free-living Protozoa In Vivomentioning
confidence: 98%